KEANEKARAGAMAN FITOPLANKTON DI PERAIRAN MANGROVE DESA PERCUT SEI TUAN KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA “Phytoplankton Diversity in The Mangrove Percut Sei Tuan River Regional Of Deli Serdang Province Of North Sumatera.” - Sangap Ginting; Yunasfi Djayus; Rusdi Leidonald (AQUACOASTMARINE, 2017)
Phytoplankton in aquatic coastal ecosystems play a major role in the food chain. This is because the role of Phytoplankton as producen in the waters of other organisms that can be used include fish. The existence of Phytoplankton in the waters is largely determined by the physicaland chemical condition of the water. Phytoplankton have a certain tolerance limits to environmental parameters so that diversity will be different. The research was conducted from April to May 2016. Samples were taken from three observation stations, at each station observations were made three replications. Sampling point is determined using purposive random sampling method.Total abudance of phytoplankton at station 1 as many as 11.400 cell/l, which consists of 16 genera, abudance of phytoplankton at statiun 2 as many 39.050 cell/l which consists of 10 genera, and abudance of phytoplankton at statiun 3 as many 48.900 cell/l which consists of 18 genera.Pearson correlation analysis phospate, nitrate, DO, and brightness was positibelly correlated with the diversity of phytoplankton while the temperature, pH, and salinity were negatively correlated with the diversity of phytoplankton.Keywords : Phytoplankton, Percut Sei Tuan River, diversity